Conformational dynamics of a lipid−interacting protein: MD simulations of saposin B - Stokeley, D; Bemporad, D; Gavaghan, D; Sansom, M (2007)
Saposin B is a water soluble alpha-helical protein which can bind to membranes and extract selected lipids, especially cerebroside sulfates. The X-ray structure of saposin B is homodimeric. There are two conformations of the dimer in the crystal-one with a closed central cavity (the AB dimer) and one (the CD dimer) with a more open cavity. We have conducted a series of short (5 ns) molecular dynamics simulations of saposin B, starting from both the AB and CD conformations and with/wi